Mitigating distress and promoting positive aspects of caring in caregivers of children and adolescents with schizophrenia: Mediation effects of resilience, hope, and social support. (9th January 2020) - Wang, Anni; Bai, Xiaoling; Lou, Ting; Pang, Jin; Tang, Siyuan
Abstract: Assistance for distressed caregivers can indirectly facilitate recovery of the people being cared for, yet how resilience, hope, and social support mediate between caregiving burden and adjustment outcomes is unclear. A structural equation model was constructed based on data from a cross‐sectional survey of 324 caregivers of children and adolescents with schizophrenia using multidimensional caregiver burden inventory, Connor‐Davidson resilience scale, Herth hope index, perceived social support scale, distress management screening measure, and positive aspects of caregiving instruments. On distress, caregiving burden had a relatively large direct effect, and an indirect effect, mainly mediated by resilience. Resilience had a greater effect than social support or hope on distress. On positive aspects of caregiving (PAC), caregiving burden had only an indirect effect, primarily via the processes from social support and resilience to hope. Hope had a significant direct effect, while resilience and support had moderate indirect effects on PAC via hope. Resilience is an important mediator between caregiving burden and distress, with a greatest effect. Resilience, hope, and social support all mediated between caregiving burden and PAC, with hope having a greatest effect. Reducing the care burden may greatly help to relieve caregiver distress. Providing needed social support, encouraging caregivers to proactively utilize the support, and enhancing resilient coping skills will be helpful in developing resilience and mitigating distress. Health professionals should assess and ameliorate burden, be particularly aware of caregiver hopes, provide formal support, and encourage informal support to promote PAC.